IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA SEMARANG - Tampubolon, John L; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Trash problem is one of many problems faced by big cities in Indonesia, including Semarang City. The trash that increases every day can certainly bring new problems to the environment as well as with health. Therefore, the government of Semarang city issued a policy of Regional Regulation number 6 of 2012 on Trash management in Semarang city. This research will further discuss about the implementation of trash management policy in Semarang city. The research results showed that the implementation of trash management policy implemented in two main stages, the trash reduction stages and trash management stages. In the implementation of these two stages there are several obstacles and also found things that become an inhibiting factors and supporting factors of trash management policy implementation in Semarang city. It also explained about trash management based on upstream and downstream management. The recommendation by this research are; improve the information dissemination on trash management to the community, improve and add facilities and infrastructure to support the implementation of trash management and improve the resources both from government agencies, communities and also private sector to jointly overcome the existing trash problem in Semarang city.